SOSIALISASI PENGGUNAAN SOSIAL MEDIA UNTUK MEMPROMOSIKAN PRODUK UMKM DI BANJAR BAJING DESA TEGAK - Dewa Nyoman Benni Kusyana (UNHI Press, 2021)
Promotional activities are one of the elements in the marketing mix that play an important role in the survival of the company, both for large companies and even SMEs. Promotion is done to introduce a product or business to consumers. The development of information technology provides opportunities for SMEs to be able to promote their products and businesses through social media such as Instagram and Facebook. This activity to promote SME products was held in Banjar Bajing, Tegak Village starting from September 18th, 2020 to September 30th, 2020 involving 31 SMEs and was carried out door-to-door to avoid crowds according to health protocols to prevent the transmission of Covid 19. The results of promotional activities show a positive trend as evidenced by an increase in sales volume and social media is an effective and efficient promotional tool to increase sales of SMEs